A linguistic analysis of definations of Islamic terms in the Oxford Advanced Learner's Dictionary (2005), the Macmillan English Dictionary for Advanced Learners (2007) and the Cambridge Advanced Learner's Dictionary (2008) - Haslina Mohd Noor (Kulliyyah of Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The aim of this dissertation is to examine the definition, spelling and pronunciation of Islamic terms as portrayed in the Oxford Advanced Learner's Dictionary (OALD, 2005), the Macmillan English Dictionary for Advanced Learners (Macmillan, 2007), and the Cambridge Advanced Learner's Dictionary (CALD, 2008). Through this research, one would be able to look at the problematic definition, spelling and pronunciation of Islamic terms in the three English dictionaries that bring about misconception, confusion and misunderstanding among dictionary users about the intended definition, spelling and pronunciation of the terms as understood in Islam. This research is based on a qualitative data collection. The Islamic terms were first identified from the OALD (2005) which served as a basis for reference of target items for the other two dictionaries. The identified Islamic terms then were examined and alternative suggestions for appropriate definition, spelling, pronunciation and transliteration of the target items as understood in Islam were provided based on the translation of the Holy Qur'an, books written by Muslim scholars and intelligentsia, Islamic encyclopedia as well as English - Arabic dictionaries. The results show that in the OALD (2005), 34 of 49 terms are intact definitions, nine of the terms are inadequately defined and six of them are inaccurately defined. 22 of 42 items in the Macmillan (2007) arc intact definitions, 11 of them arc inadequately defined and nine terms are inaccurately defined. In the CALD (2008), 15 of 32 items are intact definitions, 10 terms are inadequate definitions and seven terms are inaccurate definitions. 24 terms are inaccurately spelled while 46 items are mispronounced in the OALD (2005), 18 terms are inaccurately spelled while 39 items are mispronounced in the Macmillan (2007) and 16 terms are inaccurately spelled while 30 items are mispronounced in the CALD (2008). In brief, the misconception of Islamic terms in terms of definition, spelling and pronunciation in English dictionaries is worth acknowledging to prevent confusion and misunderstanding among dictionary users who wish to understand Islam. It is modestly presumed that this study is a contribution to Islamic lexicon in the English language dictionaries.